2015
DOI: 10.1021/acsami.5b00994
|View full text |Cite
|
Sign up to set email alerts
|

Label-free Protein Detection Based on the Heat-Transfer Method—A Case Study with the Peanut Allergen Ara h 1 and Aptamer-Based Synthetic Receptors

Abstract: Aptamers are an emerging class of molecules that, because of the development of the systematic evolution of ligands by exponential enrichment (SELEX) process, can recognize virtually every target ranging from ions, to proteins, and even whole cells. Although there are many techniques capable of detecting template molecules with aptamer-based systems with high specificity and selectivity, they lack the possibility of integrating them into a compact and portable biosensor setup. Therefore, we will present the he… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2016
2016
2018
2018

Publication Types

Select...
5
1
1

Relationship

4
3

Authors

Journals

citations
Cited by 35 publications
(22 citation statements)
references
References 40 publications
0
22
0
Order By: Relevance
“…To overcome convection it is possible to simply invert the setup and heat the cylindrical fluid column inside the flow cell from above which has been done for the detection of DNA mutations and proteins . However, for the detection of macromolecular targets such as cells or bacteria it is necessary to allow the target particles to sediment to the functional interface located on top of the copper heat provider.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…To overcome convection it is possible to simply invert the setup and heat the cylindrical fluid column inside the flow cell from above which has been done for the detection of DNA mutations and proteins . However, for the detection of macromolecular targets such as cells or bacteria it is necessary to allow the target particles to sediment to the functional interface located on top of the copper heat provider.…”
Section: Resultsmentioning
confidence: 99%
“…Changes occurring at the interface will alter its thermal resistance, which can be detected by the setup. HTM has been used for a wide range of applications including DNA mutation analysis , small molecule detection , and the detection of proteins , mammalian cells and bacteria .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although still 2 times higher (i.e. 3 nM), a promising result was reported later while employing the heat-transfer technology [44]. However, the same authors showed that the only so-far obtained LOD value of 1 nM was achieved when employing a more complex electrochemical impedance spectroscopy setup [43].…”
Section: Ara H 1 Peanut Allergen Detectionmentioning
confidence: 99%
“…Additionally, the same Ara h 1 aptamer was previously implemented in a bioassay on an FO-SPR sensing platform [33], acting as a capture receptor on a gold-coated optical fiber, while detection was performed with a gold nanoparticle-labelled anti-Ara h 1 antibody. Most recently, the same aptamer was used for label-free detection of Ara h 1 in heat-transfer resistance measurements [46]. The reported LODs for those two platforms, 15 mg/ mL and 600 ng/mL, respectively, were approximately 40 and 1.5 times higher than the value reported here.…”
Section: Magnetic Particle-based Sandwich Assaymentioning
confidence: 54%